Study on the Mechanism, Prediction, and Control of Coal Wall Spalling in Deep Longwall Panels Utilizing Advanced Numerical Simulation Methodology - Sunny Murmu; Gnananandh Budi (Geofluids)
This research looked at the occurrence of coal wall spalling, a type of longwall face failure, during the main weighing period (MWP) for panels greater than 300 m depth. FLAC3D software was exploited to simulate the ground condition of longwall panel 1 of Adriyala Longwall Project mine. The extent and severity of coal wall spalling were quantified using evaluation criteria based on the concepts of vertical stress distribution and maximum shear strain. Subsequently, a parametric analysis of thirteen factors influencing the coal wall spalling was carried out. Empirical equations for predicting coal wall spalling were suggested. Based on the parametric analysis, a coal wall spalling classification system (CWSC) chart is presented to predict spalling characteristics of coal wall that may occur at the MWP. The empirical models depicted good predictive ability with R2 values greater than 0.9. Parametric analysis revealed that coal wall spalling is highly sensitive to seam compressive strength, mining-induced stress, extraction height, and immediate roof characteristics. The CWSC system’s applicability to the five panels was in good agreement with field observations.